Pengaruh Likuiditas dan Solvabilitas terhadap Profitabilitas pada PT. Indofood CBP Sukses Makmur, Tbk. Yang terdaftar di Bursa Efek Indonesia - Muhammad Rizky Ramdaniansyah (Nusa Putra University, 2020)
The purpose of this study was to describe the liquidity, solvability and profitability of PT Indofood CBP Sukses Makmur, Tbk. and to determine the effect of liquidity and solvability on profitability. The method of analysis used in this research is quantitative descriptive analysis method. The object of this research is PT Indofood CPB Sukses, Tbk for the period 2014- 2019. The method used for this is multiple linear regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of the analysis of multiple linear regression are: Å¶ = 0.156 + 0.013 X1 + (-0,117) X2. This means that there is a positive influence on liquidity, and a negative effect on solvability on profitability. The result of the correlation coefficient analysis is 0.963 which means a strong relationship between these three variables. The coefficient of determination is 0.877, which means that 87.7% of the variation in profitability is explained by CR and DER. The research hypothesis shows that the liquidity variable is rejected on the solvability variable, meaning that liquidity has no effect and solvability has a significant effect on profitability at PT Indofood CBP Sukses Makmur, Tbk. 2014-2019 period.